PENGARUH UMUR DAN SISTIM PENANAMAN AKAR WANGI (Vetiveria zizanioides L.) DALAM PERBAIKAN KUALITAS LIMBAH CAIR PABRIK TAPIOKA - Eko Rini Indriyatie; E. Handayanto; W.H. Utomo (Universitas Tribhuwana Tunggadewi, 2008)
A series of experiment had been conducted to elucidate the effects of age and planting system of fragrant root (Vetiveria zizanoides) in improving quality of tapioca industry liquid waste. Eight treatments generated from two planting systems, i.e. hydroponics system (To) and wetland system (T1), and four levels of plant age, i.e. 7 days after planting (LiV1), 45 days after planting (L1V45), 60 days after planting (L1V60), and 75 days after planting (L1V75), were arranged in a randomized block design with three replicates. pH, BOD, COD, DO and CN values were measured periodically for 61 days. Results of the study showed that various age of fragrant root plant were capable of reducing BOD, COD and CN concentrations, as well as increasing DO concentration and pH value for the two planting systems. During remediation process, the LiV75 treatment at wetland system produced better quality of tapioca liquid waste than that of hydroponics system